2018
DOI: 10.1016/j.jbiomech.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

In situ comparison of A-mode ultrasound tracking system and skin-mounted markers for measuring kinematics of the lower extremity

Abstract: Skin-mounted marker based motion capture systems are widely used in measuring the movement of human joints. Kinematic measurements associated with skin-mounted markers are subject to soft tissue artifacts (STA), since the markers follow skin movement, thus generating errors when used to represent motions of underlying bone segments. We present a novel ultrasound tracking system that is capable of directly measuring tibial and femoral bone surfaces during dynamic motions, and subsequently measuring six-degree-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…While this study has shown promising results in the assessment of static spinal postures, more advanced scenarios could consider the assessment of dynamic spinal motion. On the human lower extremities, T-US has shown promising results in the kinematic assessment of the knee joint [50][51][52]. It was demonstrated that US showed lower kinematic errors compared to marker-based systems, with bone pins providing ground-truth data [50].…”
Section: Discussionmentioning
confidence: 99%
“…While this study has shown promising results in the assessment of static spinal postures, more advanced scenarios could consider the assessment of dynamic spinal motion. On the human lower extremities, T-US has shown promising results in the kinematic assessment of the knee joint [50][51][52]. It was demonstrated that US showed lower kinematic errors compared to marker-based systems, with bone pins providing ground-truth data [50].…”
Section: Discussionmentioning
confidence: 99%
“…While this study has shown promising results in the assessment of static spinal postures, more advanced scenarios could consider assessment of dynamic spinal motion. On the human lower extremities, T-US has shown promising results in the kinematic assessment of the knee joint [50][51][52]. It was demonstrated that the US showed lower kinematic errors compared to marker-based systems, with bone pins providing ground-truth data [50].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a 3D model of the bone surface from a CT/MRI (magnetic resonance imaging) scan was used which was fitted into the point cloud by optimization. Niu et al showed that a maximum measured root mean square error of 3.44 • and 4.88 mm could be achieved compared to intra-cortical bone pins for dynamic in-vivo tibiofemoral measurements, or even better in a cadaveric study [51,52].…”
Section: Non-invasive Proceduresmentioning
confidence: 99%